Back Cover: Aqueous‐Phase Hydrodeoxygenation of Biomass Sugar Alcohol into Renewable Alkanes over a Carbon‐Supported Ruthenium with Phosphoric Acid Catalytic System (ChemCatChem 5/2017). Issue 5 (8th March 2017) - Weng, Yujing; Wang, Tiejun; Qiu, Songbai; Wang, Chenguang; Ma, Longlong; Zhang, Qi; Chen, Lungang; Li, Yuping; Sun, Fei; Zhang, Qian
Abstract : The Cover shows the catalytic conversion of biomass hydrolysate into renewable alkanes over a Ru/C catalyst with aqueous phosphoric acid (Ru/C+H3 PO4 ), in which a high yield of C5 /C6 alkanes was obtained.In their Full Paper, Y. Weng et al. investigated the mechanism of the sorbitol hydrodeoxygenation (HDO) reaction into alkanes over a Ru/C+H3 PO4 catalyst by using a trickle‐bed reactor. Higher HDO performance might be a result of the bifunctional role of the catalytic system. These findings suggest that the downstream process of biomass hydrolysis could be directly conducted in acid aqueous phase at low reaction temperature, reducing the amount of acid waste.